Flow-diverter stents combined with flow-T stenting-assisted coiling for the treatment of a large basilar apex aneurysm: a case report with a 9-month follow-up - Wang, Hao; Zhang, Jingyu; Yang, Huajiang; Zeng, Shi; Guo, Tengyun; Xu, Lunshan; Yang, Donghong (Frontiers in Neurology, 2024)
The treatment of wide-neck, large basilar apex aneurysm is challenging either endovascular or surgical . We present a novel concept for the treatment of complex basilar apex aneurysms using flow-diverter devices combined with flow-T stenting assisted coiling technique. Assess the efficacy and safety profile of the technique in this specific anatomic condition. Case description: A patient with multiple unruptured intracranial aneurysms underwent staged treatment. A large basilar apex aneurysm was treated with a flow-diverter stent combined with a flow-T stenting assisted coiling technique in the first stage, and a giant supraclinoid aneurysm was treated with a flow-diverter stent applied in the second stage. Clinical presentations, technical details, intra-and perioperative complications, clinical and angiographic outcomes were recorded, with 9-month follow-up.The patient achieved full neurologic recovery postoperatively. Cerebral angiography performed postoperatively showed revascularization, good laminar flow, and no in-stent or adjacent stenosis. Conclusions: Flow-diverter stents combined with flow-T stenting assisted coiling for the treatment of giant basilar apex aneurysm is a feasible technique with efficacy demonstrated at 9-month follow-up. Staged endovascular treatment of multiple intracranial aneurysms may be a safe and viable option.